The Readiness of Healthcare Workers in Disaster Health Management at Primary Healthcare Facilities - Umbu Roga, Anderias (CV. Get Press Indonesia, 2026)
The rising frequency and intensity of disasters, fueled by climate change, urbanization, and population growth, challenge global health systems. Primary health care facilities act as frontline responders, ensuring early intervention and service continuity. Thus, health worker preparedness is vital for effective disaster management at this level. This study evaluated preparedness among health workers in primary facilities, focusing on knowledge, attitudes, skills, and organizational support. A quantitative descriptive-analytic, cross-sectional study involved 120 health workers (doctors, nurses, midwives, others). Data came from structured questionnaires (in-person and online). Analysis used univariate descriptives, Chi-Square tests for associations, and logistic regression for dominant factors. Results show moderate disaster preparedness overall (47.5%). Significant associations existed with education, experience, training participation, and knowledge (p < 0.05). Multivariate analysis identified disaster training as the strongest predictor (OR = 3.21; 95% CI: 1.52–6.78; p = 0.002), with trained workers over three times more likely to exhibit high preparedness. Enhancing preparedness demands ongoing training, routine simulations, better infrastructure, and standardized protocols in primary care to boost resilience and emergency response.